Terapi Sugesti dalam Perspektif Psikologi Islam (Suatu Kajian Terhadap Ayat Al-Quran dalam Penyembuhan Penyakit Psikis) - Rifyal Novalia (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
The humans' uniqueness apart from being physical creatures, humans are also psychological creatures. Physical and psychological have different power or essence, where each essence requires different needs, especially in terms of psychics when experiencing an inner conflict, the antidote needed cannot be served by medical injection since naturally, human physics does not come from material essence. There are many verses of the Qur'an that can be used as suggestions for healing psychological diseases for humans. Research of the verses of the Qur'an which was carried out using analytical methods in the Islamic Psychology perspective suggested that the content of the Qur'an in certain verses can be used as suggestions to improve the chaotic physical system into perfection of the human soul, in accordance with the nature of its creation.